Cara Melatih dan Mengembangkan Daya Ingat Anak Usia 7-11 Tahun (Studi Kasus: SD N 067690) - Panggabean, Noviyantika Azzahra; Ritonga, Fajar Utama (Medan Resource Center, 2023)
This article aims to discuss how to train and develop the memory of children aged 7-11 years at SD N 067690. In the era of globalization, the cognitive development of late-age children (7-11 years) has decreased, especially in terms of memory ability. This is indicated by the decline in academic achievement of elementary school students, especially in memorizing lessons. Basically, a child's memory can be developed through a learning process that trains thinking skills and memory. This study uses qualitative research with a descriptive approach. The data in the study were obtained from observations, interviews and hands-on practice with the children of SD N 067690. The results showed that there was progress made by students in terms of improving memory through the three methods that the researchers applied, namely the method of assembling puzzles, retelling ( story telling).